2018
DOI: 10.3847/1538-4357/aa9edb
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Reconnection in Strongly Magnetized Regions of the Low Solar Chromosphere

Abstract: Magnetic reconnection in strongly magnetized regions around the temperature minimum region of the low solar atmosphere is studied by employing MHD-based simulations of a partially ionized plasma within a reactive 2.5D multi-fluid model. It is shown that in the absence of magnetic nulls in a low β plasma the ionized and neutral fluid flows are well-coupled throughout the reconnection region. However, non-equilibrium ionization-recombination dynamics play a critical role in determining the structure of the recon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 52 publications
(79 reference statements)
6
78
4
Order By: Relevance
“…In our previous paper 32 , the numerical results demonstrated that the collisions between electrons and neutrals are not important for magnetic reconnection in low β plasmas. In order to compare with the corresponding cases in Ni et al (2018), we also ignore the collisions between electrons and neutrals in this work. The dimensionless magnetic diffusivity is…”
Section: Normalization and Initial Conditionsmentioning
confidence: 93%
See 2 more Smart Citations
“…In our previous paper 32 , the numerical results demonstrated that the collisions between electrons and neutrals are not important for magnetic reconnection in low β plasmas. In order to compare with the corresponding cases in Ni et al (2018), we also ignore the collisions between electrons and neutrals in this work. The dimensionless magnetic diffusivity is…”
Section: Normalization and Initial Conditionsmentioning
confidence: 93%
“…Our simulations are performed by using the reactive multi-fluid plasma-neutral module of the HiFi modeling framework 30,32 . Here, we normalize the equations by using the character- be uniform with a neutral particle number density of n n0 = 0.5n = 0.5 × 10 21 m −3 , and the initial ionization degree is f i0 = n i0 /(n i0 + n n0 ) = 0.01%.…”
Section: Normalization and Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…EBs result when the reconnection occurs in the upper photosphere with temperatures some 1 000-3 000 K higher than ambient (e.g., Rutten et al 2013), while UV bursts are reproduced when the reconnection is located higher in the chromosphere and entails much higher temperatures than those found in EB models, at least high enough to ionize silicon three times: 20 kK if in dense photospheric material, 80 kK at lower densities, as pointed out by Rutten (2016). It may be possible to generate temperatures as high as 25 kK through reconnection in the upper photosphere or lower chromosphere, as shown by Ni et al (2016Ni et al ( , 2018. Priest et al (2018) and Syntelis et al (2019) pointed out in a theoretical work that flux cancellation can cause simultaneous reconnection at different heights in the solar atmosphere.…”
Section: Introductionmentioning
confidence: 91%
“…If β is lower, that is, higher in the atmosphere, the plasma can be heated to higher temperatures, and in the low chromosphere gravity can hinder the formation of plasmoids (Ni et al 2016). However, the situation changes if one accounts for the presence of neutrals in the chromosphere and the reconnection in the low chromosphere can result in peak temperatures of about 30 kK (Ni et al 2018a;Ni & Lukin 2018). During reconnection, the 2D models can produce turbulent small-scale structures in plasmoids that cover a range of temperatures from 10 4 K to 10 5 K, that is, covering the temperatures expected in Ellerman bombs and UV bursts.…”
Section: Introductionmentioning
confidence: 99%